Mineralogy and phosphorus adsorption in soils of south and central-west Brazil under conventional and no-tillage systems - Fink, Jessé Rodrigo; Inda, Alberto Vasconcellos; Bayer, Cimélio; Torrent, José; Barrón, Vidal (Acta Scientiarum. Agronomy, 2014)
The low phosphorus availability in tropical and subtropical soils, normally related to adsorption of phosphate to the minerals surfaces, can be attenuated when organic matter (OM) accumulates in the soils. Herein, we report the results of long-term experiments (18–32 years) aimed at quantifying the maximum phosphorus adsorption capacity (MPAC) and its determinant mineralogical variables in Brazilian soils and at assessing the effect of no-tillage (NT) in mitigating the phosphorus adsorption of soils. The MPAC of soils ranged from 297 to 4,561 mg kg-1 in the 0.00–0.10 m layer and from 285 to 4,961 mg kg-1 in the 0.10–0.20 m layer. The MPAC was correlated with the concentrations of iron oxides, goethite and ferrihydrite, gibbsite/(gibbsite+kaolinite) ratio and the specific surface area. The OM increased in the 0.00–0.10 m layer of NT soils, which was not reflected on the decrease of MPAC for the no-tillage soils.